Palladium-Catalyzed Decarboxylative N-3-ortho-C–H Acylation of 1,4-Disubstituted 1,2,3-Triazoles with α-Oxocarboxylic Acids - Ma, Xinyuan; Huang, Hongtai; Yang, Jianhua; Feng, Xuepu; Xie, Kai (Synthesis, 2018)
An efficient palladium-catalyzed decarboxylative selective C–H acylation is reported using α-oxocarboxylic acids as the acyl source directed by 1,2,3-triazole ring. This method provides a novel access to various 1,2,3-triazole derivatives bearing diaryl ketone skeleton.
Keywords: decarboxylation; acylation; palladium; C–H activation; 1,4-disubstituted 1,2,3-triazole